Diversified carbon intensity under global value chains: A measurement and decomposition analysis. (15th October 2020) - Xiao, Hao; Sun, Kejuan; Tu, Xingwen; Bi, Huimin; Wen, Ming
Abstract: The rise and gradually developing of global value chains (GVC) have changed the essence of international trade, and further complicated the issue of carbon emission. It is of great significance to identify and study the practical carbon intensity in a country under the condition of GVC. Based on Inter-country Input-Output (ICIO) model, this paper establishes a framework for measuring the carbon intensities embodied in aggregated demand and distinguishing pure domestic demand, traditional trade, simple GVC route, complex GVC route at the global level and for 41 economies from 2010 to 2014 according to demand heterogeneity, and uses multiplicative structural decomposition analysis (SDA) method to decompose the driving factors affecting their changes. The results indicate that, in most developed countries, the carbon intensities embodied in international trade were significantly greater than pure domestic carbon intensity, whereas it was opposite in most developing countries. The carbon intensity embodied in traditional trade was generally lower than that in GVC routes, and in low carbon intensity (high carbon intensity) sub-group, the carbon intensity embodied in simple GVC route was lower (higher) than that in complex GVC route. Moreover, the emission coefficient effect was the main driver of the decline in almost all carbon intensities, especially embodied carbon intensity in GVC routes. On the contrary, the intermediate import effect was the main inhibitor, and this effect would cause more rise to embodied carbon intensity in simple GVC route, compared to embodied carbon intensity in complex GVC route. Highlights: Five types of carbon intensities based on GVC at the global level and for 41 economies were measured. Driving factors of carbon intensity changes were decomposed by multiplicative SDA. The carbon intensity embodied in traditional trade was generally lower than that in GVC routes. Emission coefficient effect drove carbon intensities down significantly in most countries. Intermediate import effect curbed the decline of embodied carbon intensities in GVC routes.